2016
DOI: 10.1590/1414-431x20154655
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy with estradiol and drospirenone improves endothelium-dependent vasodilation in the coronary bed of ovariectomized spontaneously hypertensive rats

Abstract: Drospirenone (DRSP) is a progestin with anti-aldosterone properties and it reduces blood pressure in hypertensive women. However, the effects of DRSP on endothelium-dependent coronary vasodilation have not been evaluated. This study investigated the effects of combined therapy with estrogen (E2) and DRSP on endothelium-dependent vasodilation of the coronary bed of ovariectomized (OVX) spontaneously hypertensive rats. Female spontaneously hypertensive rats (n=87) at 12 weeks of age were randomly divided into sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
4
15
0
1
Order By: Relevance
“…Another suggestion is that the beneficial effects from the treatment are probably dependent on circulating estrogen levels in the blood, since we observed that animals with normal estrogen levels (Sham) showed the benefits generated by the treatment. In view of this hypothesis, we suggest that the castration may have caused a reduction in the beneficial effects of estrogen, perhaps by reduction of its receptors in coronary arteries of the hypertensive rats, as previously showed (Borgo et al, 2016). …”
Section: Discussionsupporting
confidence: 73%
“…Another suggestion is that the beneficial effects from the treatment are probably dependent on circulating estrogen levels in the blood, since we observed that animals with normal estrogen levels (Sham) showed the benefits generated by the treatment. In view of this hypothesis, we suggest that the castration may have caused a reduction in the beneficial effects of estrogen, perhaps by reduction of its receptors in coronary arteries of the hypertensive rats, as previously showed (Borgo et al, 2016). …”
Section: Discussionsupporting
confidence: 73%
“…Moreover, adult female rats exhibited higher eNOS activity and/or expression than males. These data suggest a higher protected status in adult females and are consistent with other studies showing that treatment with estradiol and progesterone increases eNOS-derived NO production both in isolated endothelial cells and in vascular tissue [61,62]. The protective effect of estrogens and progesterone is absent in 6-day-old rats since their gonads are not fully mature and the levels of these hormones are much lower compared with adults.…”
Section: Discussionsupporting
confidence: 91%
“…Premenopausal women undergo fluctuations in E2 and P4 during the menstrual cycle [ 38 , 40 ]. Exogenous administration of E2 and P4 has demonstrated to provide cytoprotection against several different acute and chronic myocardial stressors [ 17 , 22 , 26 , 27 , 44 , 45 ]. The role of endogenous hormones providing cytoprotection against DOX-induced myocardial dysfunction is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that heightened endogenous E2 levels did not partly suppress DOX-induced cardiotoxicity in SHRs. SHRs are known to already possess cardiac damage prior to DOX treatment [ 27 , 42 , 46 ]; therefore, a non-hypertensive rat model should be used for further investigations. Collectively, our study provides the first evidence that DOX treatment during a specific estrous stage can influence the extent of DOX-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation